Comparison between the induced membrane technique and distraction osteogenesis in treating segmental bone defects: An experimental study in a rat model. - Zhen Shen; Haixiong Lin; Guoqian Chen; Yan Zhang; Zige Li; Ding Li; Lei Xie; Yue Li; Feng Huang; Ziwei Jiang (PLoS ONE, 2019)
Previous studies have suggested that treatment plans for segmental bone defects (SBDs) are affected by the bone defect sizes. If the selected treatment was not the most appropriate, it would not contribute to bone healing, but increase complications. The induced membrane technique (IM) and distraction osteogenesis (DO) have been proved to be effective in treating SBDs. However, the differences between the two in therapeutic effects on SBDs with different sizes are still unclear. Thus, we aimed to observe the effects of IM and DO on different sizes of SBDs and to further determine what method is more appropriate for what defect size. Rat models of 4-, 6-and 8-mm mid-diaphyseal defects using IM and DO techniques were established. X-rays, micro-CT, histological and immunohistochemical examinations were performed to assess bone repair. Faster bone formation rate, shorter treatment duration, higher expressions of OPN and OCN and higher parameters of bone properties including bone mineral density (BMD), bone volume/total tissue volume (BV/TV), mineral apposition rate (MAR) and mineral surface/bone surface (MS/BS) were found in 4-mm SBDs treated with DO than in those with IM treatment. However, the results were reversed and IM outperformed DO in bone repair capacity for 8-mm SBDs, while no significant difference emerges in the case of 6-mm SBDs. This study suggests that the therapeutic effects of IM and DO may be subjected to sizes of bone defects and the best treatment size of defects is different between the two. For small-sized SBDs, DO may be more suitable and efficient than IM, but IM has advantages over DO for over-sized SBDs, while DO and IM show similar bone repair capability in moderate-sized SBDs, which would offer a new insight into how to choose DO and IM for SBDs in clinical practice and provide references for further clinical research.